Wisdom Etic in the Dedactic of Budi Pekerti Luhur on Javanese Believe - Suwardi, Suwardi (UI Scholars Hub, 2010)
This article aims to describe wisdom etic in the dedactic of budi pekerti luhur on Javanese believe (vivify). The description is provided using ethnographic analytic on the actualization of budi pekerti luhur on Javanese believe. The data collection was held by taking participant observation and indepth interview with the informant using snowballing method. The study shows that budi pekerti luhur on Javanese believe can be categorized into two matters: The first, wisdom etic in congregation level i.c. life that always attitude of: (1) pasrah, submit to God totally (sumarah), and (2) the honest and sincere. The second, help mutual. This wisdom etic as actualization of concept tapa ngrame. Tapa ngrame conducted by sepi ing pamrih spirit than as shape of world view on memayu hayuning bawana. This way vivify believe that their the next time life can achievement of the desired high level on manunggaling kawula-Gusti.